Comunidade microbiana do solo e seleção rizosférica pelo milho e Urochloa ruziziensis em sistema consorciado com aplicações de calcário e fosfogesso - Bossolani, João William [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Combining lime (L) with phosphogypsum (PG) is a strategy that plays a significant role in shaping soil chemistry and the soil microbiome. These factors have a notable impact on which microbe can be selected by the rhizospheres of co-cultivated maize and ruzigrass. Grasping this influence is vital for enhancing the growth and well-being of these paired crops. The present study aims to evaluate the effect of long-term surface application of L and/or PG on the assembly and selection of soil microbial community during maize intercropped with ruzigrass. Here, we hypothesized that in a intercropping system, plants established in soils with different levels of fertility due to application of L and PG presents different microbe associations. The following treatments were evaluated: i) control, ii) phosphogypsum (PG; 10 t ha-1), iii) lime (L; 13 t ha-1), and iv) combination of L with PG (LPG). Our findings indicated that the impact of L and PG on soil microbial functions depends on intricate relationships between physical changes, crop growth, and microbial reactions. Specific microorganisms were found in maize and ruzigrass root zones, differing from bulk soil. This highlights the connection between plant-microbe interactions, soil enhancements, and microbial community dynamics in agriculture. Results indicate plant-driven microbial selection, influenced mainly by soil amendments, particularly in nitrogen cycling and mycorrhizal presence due to LPG treatment. Further research is needed to fully understand intercropped plant-driven rhizosphere community selection.
Shifts in soil microbial communities and rhizosphere selection in a maize-ruzigrass intercropping system managed with soil amendments
Keywords: Liming; Soil conditioner; Rhizosphere; Zea mays (L.); Urochloa ruziziensis; Soil microbiology